PENINGKATAN PEMBERDAYAAN UMKM DAN PENGEMBANGAN LAHAN INOVASI MELALUI EKONOMI KREATIF DI KELURAHAN PETAMANAN KOTA PASURUAN - Yufenti Oktafiah; Sri Hastari; Dwita Laksmita R (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2023)
UMKM play an important role in the national economy. The contribution of UMKM is not only in providing employment but also contributing to the Gross Domestic Product (GDP). Empowerment of UMKM is one of the strategic and appropriate steps in the context of improving and strengthening the basic economic life of the people for most of the Indonesian people, especially in order to create new jobs to reduce unemployment and social inequality. The purpose of this service activity is to support economic recovery after the pandemic and help UMKM in the surrounding area. This activity is carried out by means of socialization with the aim of providing knowledge to UMKM about what branding is, how to determine targets and market segments, providing training on how to apply social media, training UMKM to be able to do packaging to support the process of applying marketplaces. The results obtained from this activity, the community is also expected to gain new knowledge with the socialization of digital marketing, business legality and food safety in order to help the community to adapt to life with increasingly advanced technological developments and the products produced are registered and have their own identity. Regarding the potential for educational land tourism and innovation, land managers can be motivated to develop urban farming tourism. The surrounding community, especially business people, know the importance of marketing and branding strategies with digital marketing for the UMKM products they sell.